2020
DOI: 10.1210/clinem/dgaa644
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent Fasting Improves Cardiometabolic Risk Factors and Alters Gut Microbiota in Metabolic Syndrome Patients

Abstract: Context Intermittent fasting (IF) is an effective strategy to the improvement of cardiometabolic health. Objective To examine the effects of IF on cardiometabolic risk factors and the gut microbiota in patients with metabolic syndrome (MS). Design Randomized clinical trial. Setting Community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
131
0
16

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(148 citation statements)
references
References 45 publications
1
131
0
16
Order By: Relevance
“…The production of short-chain fatty acids increased and the circulating levels of lipopolysaccharides decreased. These alterations were significantly associated with improved cardiovascular risk factors and reduced fat mass, ameliorated oxidative stress, modulated inflammatory cytokines and improved vasodilatory parameters and led to distinct genetic shifts of carbohydrate metabolism in the gut community [ 44 ]. Maifeld A, et al examined a fasting program which started with two calorie-restricted vegan days (max 1200 kcal/day), then 5-days with a daily nutritional energy intake of 300–350 kcal/day, followed by a modified DASH diet in patients with metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…The production of short-chain fatty acids increased and the circulating levels of lipopolysaccharides decreased. These alterations were significantly associated with improved cardiovascular risk factors and reduced fat mass, ameliorated oxidative stress, modulated inflammatory cytokines and improved vasodilatory parameters and led to distinct genetic shifts of carbohydrate metabolism in the gut community [ 44 ]. Maifeld A, et al examined a fasting program which started with two calorie-restricted vegan days (max 1200 kcal/day), then 5-days with a daily nutritional energy intake of 300–350 kcal/day, followed by a modified DASH diet in patients with metabolic syndrome.…”
Section: Resultsmentioning
confidence: 99%
“…Intermittent fasting, another recently popular diet, led to changes in the microbiome as well as improvement in metabolic parameters ( 138 ). Eight weeks of intermittent fasting revealed that the community structure of the intestinal microbiota was not significantly changed overall, but there were changes in the abundance of Ruminococcaceae at the family level and Roseburia at the genus level.…”
Section: Modulation Of the Microbiota By Dietmentioning
confidence: 99%
“…Eight weeks of intermittent fasting revealed that the community structure of the intestinal microbiota was not significantly changed overall, but there were changes in the abundance of Ruminococcaceae at the family level and Roseburia at the genus level. This was accompanied by an increased production of SCFA, decreased circulating levels of lipopolysaccharide (LPS) and inflammatory cytokines, ameliorated markers of oxidative stress, improved vasodilatory parameters, and reduced subject body fat mass ( 138 ). There is great need for further research on the health benefits of fasting and the role it plays in autophagy and cellular regeneration, especially in the liver.…”
Section: Modulation Of the Microbiota By Dietmentioning
confidence: 99%
“…Calorie restriction is an effective management strategy for CMRFs (6). Intermittent fasting (IF), an important measure of energy restriction, also significantly improves metabolic disease (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%